Pole length affects cross-country skiers` performance in an 80-m double poling trial performed on snow from standing start - Hansen, E. A.; Losnegard, T. (Sports Engineering, 2010)
We investigated the hypothesis that longer and shorter poles would be faster and slower, respectively, than poles of self-selected length in all-out double poling. Eight elite cross-country skiers performed 80 m all-out double poling on snow performed from a standing start. Three trials with each of the pole lengths: self-selected, 7.5 cm shorter, and 7.5 cm longer than self-selected were performed. Time was recorded every 20 m and skiers were filmed during the last 40 m for calculation of cycle rate and length. Times at 80 m were 0.9 ± 0.7% shorter with longer poles than with self-selected poles (p <= 0.05), while they were 1.2 ± 1.0% slower with shorter poles (p <= 0.05). Much of these differences were established within the first 20 m. Calculated lead at 80 m with longer poles was 0.88 ± 0.65 m over self-selected poles (p <= 0.05). Mean cycle rate and length ranged from 1.35 to 1.45 Hz and from 4.84 to 5.52 m, respectively, across pole lengths (p > 0.05).